The Influence of Training and Development on Employee Performance: A Study of Co-operatives in Surkhet - Gautam, Ramesh Prasad (Journal of Musikot Campus, 2025)
The aim of this study is to examine the influence of training and development on employee performance. Employee performance is a dependent variable, while training (identifying training requirements, choosing trainees, and designing training program) is considered an independent variable. Surveys and questionnaires served as primary data collection methods for the article. The statistical sample for this research was drawn from cooperative organizations in the Surkhet District. A total of 325 employees participated in this survey, completing a self-administered questionnaire distributed via convenience sampling. Regression and descriptive analysis were conducted on the data using the statistical program SPSS 25. The impact of each independent variable on overall employee performance was examined through the development of three hypotheses. Employee performance, particularly in cooperative organizations, is significantly impacted by the design of training courses and the selection of trainees. Similarly, training needs identification plays a significant role in employee performance in cooperative organizations. The findings also suggest a connection between workers’ job performance and efficient training. Training courses motivate employees to enhance their performance and skills, boosting organizational productivity. As a result, organizational requirements and goals should guide training design. Practical training is a deliberate intervention created to achieve the knowledge required for enhanced worker productivity. The study highlights the potential for training programs to enhance job satisfaction, commitment, and collective empowerment among employees. Organizations should prioritize well-structured training initiatives aligned with their strategic objectives to maximize employee performance and productivity.